2012
DOI: 10.2340/00015555-1169
|View full text |Cite
|
Sign up to set email alerts
|

Profile and Pattern of Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis in a General Hospital in Singapore: Treatment Outcomes

Abstract: Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are rare, but potentially life-threatening, reactions to medications. Both conditions have significant morbidity and mortality. The aim of this study was to document the epidemiological features, aetiologies, treatment and clinical outcomes of retrospectively reviewed data of all patients with SJS or TEN treated from January 2004 to November 2010 in a general hospital. There were 18 cases of SJS, seven cases of SJS/TEN overlap and three cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
67
4
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(88 citation statements)
references
References 38 publications
9
67
4
8
Order By: Relevance
“…HLA-B*5801 allele is another genetic marker reported to have strong association with allopurinol-induced SJS/TEN. 21 In Europe & Asia, allopurinol is commonly reported offending drug for SJS & TEN 18 whereas in present study, only 1 case of allopurinol-induced TEN was reported. Few cases of SJS/TEN due to antituberculars (isoniazid), cytotoxic drugs (lenalidomide, methotrexate), antimalarials (artesunate), antileprotics (clofazimine), antiamoebic (metronidazole) and antidepressant (reboxetine) were also reported in our study.…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…HLA-B*5801 allele is another genetic marker reported to have strong association with allopurinol-induced SJS/TEN. 21 In Europe & Asia, allopurinol is commonly reported offending drug for SJS & TEN 18 whereas in present study, only 1 case of allopurinol-induced TEN was reported. Few cases of SJS/TEN due to antituberculars (isoniazid), cytotoxic drugs (lenalidomide, methotrexate), antimalarials (artesunate), antileprotics (clofazimine), antiamoebic (metronidazole) and antidepressant (reboxetine) were also reported in our study.…”
Section: Discussioncontrasting
confidence: 44%
“…19 Penicillins and cephalosporins were the commonly reported causative drugs from Japan & Singapore. 17,18 In present study, among β-lactam antibiotics, cephalosporins were implicated in 4 cases. Fluoroquinolones were commonly reported from Indian state, Gujarat & Karnataka.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The syndrome is causes are certain medications (such as lamotrigine), but it can also be due to infections, or more rarely, cancers, or hypersensitivity reaction to some compounds [1,2]. The blisters and erosions in SJS cover between 3% and 10% of the entire body surface [3]. It is associated with factors ranging from immunoreactions, infections, genetic factors, and adverse drug reactions [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The blisters and erosions in SJS cover between 3% and 10% of the entire body surface. 3 It is associated with factors ranging from immunoreactions, infections, genetic factors, and adverse drug reactions. 4,5 Immunocompromised patients who are slow acetylators and brain tumor patients on anticonvulsant drugs who are undergoing radiotherapy are usually more prone to SJS.…”
Section: Introductionmentioning
confidence: 99%